(untitled) - Keishi, Ohara (Tokyo, Japan, 1957)
PART ONE: GENERAL OUTLINE ; PART TWO: THE OPENING OF THE PORTS AND EARLY TRADE RELATIONS BETWEEN JAPAN AND TH UNITED STATE....
Keywords: Nhật Bản,Japan; Điều kiện kinh tế,Economic conditions